Revisiting Contemporary Qur’anic Studies in Indonesia: A Critical Case Study of The Living Qur’an Method at IAIN Kediri - Hakamah, Zaenatul; Millah, Dhiyaatul; Avicena, Azra Jinggan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This study critically examines the implementation of the Living Qur’an method in student research at the Qur’anic Studies and Tafsir Programme of IAIN Kediri. It addresses a persistent methodological problem, namely the tendency of student research to adopt descriptive-phenomenological approaches without sufficient integration with textual analysis, exegetical traditions, and the framework of ʿUlūm al-Qur’ān. Using a qualitative case study design, data were collected from thirteen undergraduate theses employing the Living Qur’an approach, in-depth interviews with supervisors, and institutional curriculum and academic guideline documents. Data were analysed through an interactive model focusing on text–phenomenon correlation, depth of tafsir engagement, and normative–contextual integration. The findings reveal that most student research positions the Living Qur’an primarily as a sociological-descriptive approach, resulting in weak analytical connections between religious practices, Qur’anic texts, and interpretive traditions. Only a small proportion of studies demonstrate systematic integration of field data with exegetical analysis and relevant tafsir literature. These results indicate the absence of clear operational methodological standards in student-based Living Qur’an research. This study contributes by formulating practical methodological indicators and reaffirming the disciplinary position of the Living Qur’an within Qur’anic sciences and tafsir studies. It is expected to serve as a foundation for improving research quality in Islamic higher education institutions.